The shelf life of pork depends on its quality and microbial and non-microbial meat destructors - I. Y. Stronskyi; M. R. Simonov; Y. S. Stronskyi (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
This work aimed to establish the maximum shelf life of pork of different quality classes depending on the action of non-microbial and microbial destructors. To achieve this goal, samples were taken from the longest back muscles of domestic and industrial pig carcasses. Depending on the results of organoleptic research, pork was divided into three quality classes: 1) NOR (close to optimal quality indicators), 2) PSE (pale, soft, exudative), and 3) DFD (dark, firm, dry). After that, each of the samples was divided into 1  equal parts and placed for storage in a refrigerator (t = 3 ± 1 °C). Each day, one part of the samples was used for laboratory research. The purpose of laboratory research was to establish the freshness of meat by determining the reaction to peroxidase, amino-ammonia nitrogen, reaction to ammonia with Nessler's reagent, and the content of short-chain fatty acids. In addition, the level of MAFAnM was determined. The results of laboratory studies showed that the fastest signs of spoilage were registered in pork, with signs of PSE obtained after the slaughter of pigs on small farms. The first signs of deterioration appeared already on the sixth day of storage. The second fastest spoilage rate (on the eighth day) was meat samples of the PSE quality class taken from pigs of industrial origin. At the same time, the highest increase in microbial contamination during storage was registered in meat samples of industrial origin with signs of DFD. We found that the microbial contamination of pork depends not only on the initial contamination at the production site but also on the quality class of the meat. On the 12th day of pork storage, only NOR-class meat samples of industrial origin remained fresh. Comparing meat samples of the same quality classes, asserting a shorter shelf life and a higher risk of meat products obtained due to domestic origin and backyard slaughter of pigs is possible. The main reason is a combination of factors, the main of which are the impossibility of observing proper hygienic conditions for animal slaughter, poor bleeding, unbalanced diet, and others.